Kesiapsiagaan Siswa Dalam Menghadapi Bencana Gempa Bumi Di Tingkat SLTP Di Kecamatan Tanantovea Kabupaten Donggala - Amalia, Yuli; Rahmawati (Jurpis: Jurnal Pendidikan Ilmu Sosial, 2024)
The aim of this research is to find out the level of students' preparedness for earthquake disasters. This type of research is qualitative descriptive research with a survey method with the population being junior high school students where schools are selected based on several conditions, two schools were selected. The total number of respondents taken from 2 schools, SMPN 2 and SMPN 4 Tanantovea, was 49 students. Data were taken from a questionnaire that had been modified by the author. The results of the research show that the knowledge aspect of SMPN 2 students is in the low category of 14%, for SMPN 4 the percentage of 14% is also in the low category, the emergency response plan aspect of SMPN 2 students is in the low category of 12%, for SMPN 4 students is in the low category. 15% in the low category, the early warning aspect of SMPN 2 students in the percentage of 14% in the low category, for SMPN 4 students in the percentage of 13% in the low category, and the resource mobilization aspect of SMPN 2 students in the percentage of 15% in the low category, and for SMPN 4 students in the the percentage of 16% is in the low category. So the overall results conclude that students' preparedness in facing earthquake disasters at the junior high school level in Tanantovea District, Donggala Regency is still in the low category.